Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Problem Based Learning (PBL) Pada Mata Pelajaran PKN Kelas V SD Negeri 15 Pekanbaru - Anisa Putri Ardana; Salman Salman; Sakban Sakban (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Problem Based Learning (PBL) is a teaching and learning process in the classroom where students are first asked to observe a phenomenon. Then students are asked to record the problems that arise, after that the teacher's job is to stimulate critical thinking in solving existing problems. The teacher's task is to direct students to ask questions, prove assumptions, and listen to different perspectives among them. The problems in this study are (1) Can Problem-Based Learning (PBL) improve student learning outcomes in Civics class V at SD Negeri 15 Pekanbaru (2) How is the effect of student learning outcomes with the Problem-Based Learning (PBL) model in Civics class V at SD Negeri 15 Pekanbaru. This research includes Classroom Action Research (PTK) which was conducted in two cycles using the Problem-Based Learning (PBL) method. Each cycle consists of four stages, namely design, implementation, observation, and reflection. The subjects of this research were fifth-grade students of SD Negeri 15 Pekanbaru, totaling 35 students. The research data was obtained using teacher and student observation sheets and student test results, then the data was analyzed using the percentage formula. The results obtained were (1) teacher activity in cycle I using a problem-based learning model from 78.75% to 91.25% in cycle II, (2) student activity in cycle I using the Problem-Based Learning (PBL) model 50.48% to 85.26%, and, (3) student learning outcomes in Civics subjects in cycle I using problem-based learning 40% to 94.28% in cycle II. This shows that student learning outcomes in Civics subjects using problem-based learning models show very positive results. Based on the results of this study can improve student learning outcomes to be more active and the ability of teachers to improve for the better.